Patterns in the plankton – Spatial distribution and long-term variability of copepods on the Agulhas Bank. (April 2023) - Huggett, Jenny A.; Noyon, Margaux; Carstensen, Jacob; Walker, David R.
Abstract: Copepods dominate the zooplankton community on the broad Agulhas Bank off southern Africa, where they provide an important food resource for pelagic fish and other biota. Previous studies have shown the dominant copepod Calanus agulhensis, which may comprise up to 80% of copepod biomass, to be strongly associated with the productive cold ridge of upwelled water on the central (CAB) and eastern (EAB) Agulhas Bank. However, there is little information available on other copepod taxa, and whether the Agulhas Bank community has changed over time in response to environmental variability or other ecosystem changes, such as the recent eastward shift in pelagic fish distribution. We use in situ temperature, chlorophyll a (chl a ), and zooplankton data collected annually in late spring to explore spatio-temporal variability in copepod biomass and species composition on the Agulhas Bank over a 24-year period, from 1988 to 2011. Functional traits were used to interpret the observed patterns. Total copepod abundance and biomass were concentrated on the outer central and eastern shelf (>100 m), coincident with the region of elevated chl a at 30 m, and largely downstream from cooler subsurface water linked to the cold ridge and coastal upwelling. Current and cruise-feeding herbivores C. agulhensis and the smaller Para- and Clausocalanidae collectively accounted for 73% and 54% of total copepod biomass and abundance respectively, driving the main patterns for total biomass. C. agulhensis copepodites showed an ontogenetic shift in distribution with distance offshore and downstream from the cold ridge, and accumulation of older stages near the southern tip of the bank. The upwelling specialist Calanoides natalis was closely associated with shelf-edge upwelling, particularly near the Agulhas Bight, but was low in biomass compared to the Benguela upwelling system. The current/cruise-feeding detritivores Metridia lucens and the Oncaeidae were largely associated with the western sector of the bank but showed different niche preferences. M. lucens inhabited the chl-rich outer bank of the western Agulhas Bank (WAB), likely a continuation of the southern Benguela upwelling system community, while oncaeid biomass was associated with deeper thermoclines across the WAB and western part of the CAB that often feature accumulations of the gelatinous zooplankton they feed on. Centropages spp. and the Oithonidae, mainly omnivorous ambush feeders, were associated with the inner to mid-shelf region of the WAB and CAB, away from the main influence of the Agulhas Current. Centropages biomass aligned well with elevated chl a on the inner WAB, likely an extension of the Benguela community ( C. brachiatus ), and with the cold ridge over the inner CAB shelf, matching earlier patterns linked to C. chierchiae . Oithonidae were widespread but low in biomass, and scarce over the Agulhas Current-influenced outer shelf, suggesting a suboptimal environment overall for this group compared to the cooler Benguela upwelling region. Current-feeding and omnivorous Pleuromamma spp., known to be deep vertical migrators, were concentrated beyond the WAB shelf edge. Total copepod biomass showed a significant decline over the entire Agulhas Bank during the 24-year time series, as did all stages of C. agulhensis, including large nauplii, and the small calanoids (Paracalanidae and Clausocalanidae). No long-term trends were observed for the other copepod taxa. We found no trends in temperature, but a significant but weak (1.5% yr −1 ) increase in chl a at 30 m. Although there was no obvious shift in copepod biomass in response to the eastward shift in pelagic fish in ca. 1996, there were significant negative relationships between copepod biomass (for total copepods and C. agulhensis ) and pelagic fish biomass (total, anchovy and redeye) from 1988 to 2011, with significantly lower copepod biomass after 1998 compared to before. This suggests predation pressure has an important top-down influence on copepod biomass on the Agulhas Bank. Bottom-up forcing from environmental drivers cannot be ruled out, however, despite ambiguous results from in situ and remote data series, and long-term warming due to climate change is expected to negatively impact ecosystem productivity at the large scale.